Guinea-Bissau School Autonomy and Accountability : SABER Country Report 2017 - Merchant, C. Melissa; Demas, Angela; Gardner, Emily Elaine; Khan, Myra Murad (World Bank, Washington, DC, 2018)
In 2011, the World Bank Group commenced a multiyear program designed to support countries in systematically examining and strengthening the performance of their education systems. Part of the World Bank's Education Sector Strategy, the evidence‐based initiative called SABER (Systems Approach for Better Education Results) is building a toolkit of diagnostics for examining education systems and their component policy domains against global standards, best practices, and in comparison with the policies and practices of countries around the world. By leveraging this global knowledge, the SABER tools fill a gap in the availability of data and evidence on what matters most for improving the quality of education and achieving better results. This report discusses the results of applying the SABER School Autonomy and Accountability (SAA) tool in Guinea‐Bissau.